Identification and characterization of endophytic fungi found in plants from northeast Brazilian mangroves: a review (Research, Society and Development, 2022)
Mangroves constitute an ecosystem formed by different classes of living organisms. Due to its diversity, it has an ecological and environmental value that human activities can threaten. Endophytic fungi, found inside plant tissues, can produce substances of biotechnological value, such as antibiotics and other active principles with pharmacological properties. Therefore, this narrative review of the literature carried out through the analysis of articles found in different databases, such as: 'CAPES Journal Portal,' 'Web of Science,' 'SciElo,' 'Pubmed,' among others, highlights the importance of identifying, characterizing, and isolating endophytic fungi found in Brazilian mangroves and their relevance to the prospection of substances of high biotechnological value to the society. As well as to assist in understanding the ecological dynamics of mangroves in Brazil.